Angioimmunoblastic T-cell lymphoma with predominant CD8+ tumor-infiltrating T-cells is a distinct immune pattern with an immunosuppressive microenvironment - Chen, Zihang; Zhu, Qiqi; Deng, Xueqin; Yao, Wenqing; Zhang, Wenyan; Liu, Weiping; Tang, Yuan; Zhao, Sha (Frontiers in Immunology, 2022)
Background: Angioimmunoblastic T-cell lymphoma (AITL) has a rich tumor microenvironment (TME) that typically harbors plenty of CD4+tumor infiltrating lymphocytes, (TIL)-T-cells (so called common AITL). Nonetheless, AITL with large numbers of CD8+TIL-Ts that outnumber CD4+cells have been observed (CD8-predominant AITL). However, detailed comparison of CD8-predominant AITL and common AITL are still lacking. Methods: We compared clinicopathological features, TIL subsets, TME T cell receptor-β (TRB), and immunoglobulin heavy chain (IGH) repertoires, and gene expression profiles in six CD8-predominant and 12 common AITLs using case-control matching (2014 to 2019). Results: Comparing with common AITLs, CD8-predominant AITLs showed more frequent edema (P = 0.011), effusion (P = 0.026), high elevated plasma EBV-DNA (P = 0.008), and shorter survival (P = 0.034). Moreover, they had more pronounced eosinophil increase (P = 0.004) and a higher Ki67 index (P = 0.041). Flow cytometry revealed an inverted CD4/CD8 ratio in TIL-Ts and lower TIL-B proportions (P = 0.041). TRB repertoire metrics deteriorated, including lower productive clones (P = 0.014) and higher clonality score (P = 0.019). The IGH repertoire was also narrowed, showing a higher proportion of the top 10 clones (P = 0.002) and lower entropy (P = 0.027). Gene expression analysis showed significant enrichment for upregulated negative regulation of immune system processes and downregulated T-cell activation and immune cell differentiation. Conclusion: Our findings demonstrated that CD8-predominant AITL is a distinct immune pattern of AITL characterized by anti-tumor immunity impairment and an immunosuppressive microenvironment. These characteristics can interpret its severe clinical manifestations and poor outcomes.